Non-Muslims’ beliefs about Islamic advertising: another exploratory study in Malaysia - Shafiq, Ali (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper explored Non-Muslims’ beliefs about Islamic advertising. It adapted thought elicitation for data collection using ‘word association technique’. When compared to Muslims, some similar as well as very dissimilar beliefs were extracted regarding Islamic advertising. While they were categorized into the same dimensions as their Muslims counterparts, this research also extracted some different dimensions and sub-dimensions. This research develops the concept of Islamic advertising from the point of view of non-Muslims, as previously only Muslims’ views were available. It will help the theorists and the advertisers equally. With a growing concern for business ethics, this research attempts to eradicate the ill-effects of contemporary advertising by providing sound evidence to revise advertising policies. It is the first of its kind and adds to the developing field of Islamic marketing.